A systematic literature review on the contributing factors of safety culture in mining industry - Azizul Helmi, Sofian; Siti Noraishah, Ismail (Penerbit UMT, 2024)
Governments make billions of dollars from mining activity. The rates of fatalities and disasters related to the mining industry seem to be worrying worldwide. One of the solutions is to promote and strengthen a good safety culture practice at the mine site. However, there is still a lack of papers discussing the contributing factors of safety culture in the mining industry. Thus, this systematic review aimed to investigate the contributing factors of the safety culture or mining industry from 2020 to August 2023 using Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). Based on SLR, the top five contributing factors to safety culture were safety competency, management commitment, safety training, the safety environment, and safety rules. In order to help mine owners, this systematic review study will provide the latest knowledge on the contributing factors to creating a safety culture in the mining industry. The study also takes into account miners, the government, and policymakers so that all parties may work together to reduce mining accidents in the future.